Meningkatkan Karakter Gotong Royong Peserta Didik dalam Pembelajaran PAKBP dengan Model PBL Fase C Kelas V di SDN 23 Periang - Christine Yossy Meinarty; Fr. Wuriningsih; Budi Hartono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to describe the extent to which the application of the Problem Based Learning (PBL) model in PAKBP subjects can improve the mutual cooperation character of class V Phase C students at SDN 23 Periang, Kayan Hilir District, Sintang Regency. This type of research is Classroom Action Research (PTK), with two cycles, namely cycle 1 and cycle 2. The activity stages are planning, implementation, observation, analysis and reflection which are carried out face to face. The research is entitled "Improving Students' Mutual Cooperation Character in PAKBP Learning Using the PBL Phase C Model for Class V at SDN 23 Periang." The research was carried out at SDN 23 Periang from 13 to 20 September 2024. The research subjects were students in class 5 Phase C. The object of the research was the application of the Problem Based Learning (PBL) model in improving the mutual cooperation character of students in class V Phase C. Data collection was carried out by means of direct observation and distribution of questionnaires. Data analysis techniques: data collection, data condensation, presentation and drawing conclusions. The research results show that the PBL model can be an effective approach in developing students' cooperative character. The results of the research also show that there is a significant increase in the mutual cooperation character of students, and is able to encourage the growth of an attitude of mutual cooperation. Through group activities and structured discussions, students are trained to respect each other's differences of opinion, share responsibility, share information and collaborate to achieve common goals. .